1988
DOI: 10.1016/0014-5793(88)80135-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH and cell adhesion to solid substrate

Abstract: It was shown that activation of the Na+/H+ antiporter resulting in an increase of intracellular pH (pH,) by 0.24.3 is a necessary stage of cell stimulation by soluble growth factors. Solid substrate can also be formally regarded as a growth factor since adhesion stimulates proliferation of various cell types. In the present study we have found that the attachment of mouse embryo fibroblasts to solid substrate is followed by an increase of pH, by approx. 0.3 units. pH shift occurs after the cell attaches to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

1991
1991
1998
1998

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…A number of studies have demonstrated a correlation between the extent of cell flattening and pHi (29)(30)(31)(32) In the present studies with cytotactin, although cells were initially maintained in a more rounded state, the correlation between rounding and inhibition of proliferation was-not absolute. Consistent with this, in the presence of cytotactin, fibroblasts pretreated with nocodazole rapidly flattened but DNA synthesis was still inhibited.…”
Section: Discussionmentioning
confidence: 58%
“…A number of studies have demonstrated a correlation between the extent of cell flattening and pHi (29)(30)(31)(32) In the present studies with cytotactin, although cells were initially maintained in a more rounded state, the correlation between rounding and inhibition of proliferation was-not absolute. Consistent with this, in the presence of cytotactin, fibroblasts pretreated with nocodazole rapidly flattened but DNA synthesis was still inhibited.…”
Section: Discussionmentioning
confidence: 58%
“…6, we propose that the cytoplasmic regulatory domain (R) mediates extracellular signals through interaction with the H+-sensor. Extracellular signals are mediated through phosphorylationinduced conformational change of R. At this stage we would like to speculate that also activation of NHE1 in response to intracellular signals such as osmotic stress (2,7) or cell spreading (25,26) might be transmitted to the H+-sensor through interaction of R with cytoskeletal elements. We have now developed appropriate molecular probes and a cell system to test the bases of this hypothetical model.…”
Section: Discussionmentioning
confidence: 99%
“…[Ca++]i increases before cell spreading, although this increase has been observed when the cells are plated on nonspecific substrata (Kruskal et al, 1986;Kruskal and Maxfield, 1987). A rise in cytoplasmic pH (pHi) has been correlated with cell adhesion to the ECM (Margolis et al, 1988;Schwartz et al, 1989Schwartz et al, , 1990Ingber et al, 1990). The alkalinization of pH; in spread fibroblasts is thought to be regulated by clustering # 1-integrin that enhances the transmembrane Na+/H+ antiport (Schwartz et al, 1991).…”
Section: Introductionmentioning
confidence: 99%